Liver injury after SARS‐CoV‐2 vaccination: Features of immune‐mediated hepatitis, role of corticosteroid therapy and outcome. Issue 6 (23rd June 2022) - Efe, Cumali; Kulkarni, Anand V.; Terziroli Beretta‐Piccoli, Benedetta; Magro, Bianca; Stättermayer, Albert; Cengiz, Mustafa; Clayton‐Chubb, Daniel; Lammert, Craig; Bernsmeier, Christine; Gül, Özlem; la Tijera, Fatima Higuera‐de; Anders, Margarita; et al.
Abstract: Background and Aims: A few case reports of autoimmune hepatitis–like liver injury have been reported after severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) vaccination. We evaluated clinical features, treatment response and outcomes of liver injury following SARS‐CoV‐2 vaccination in a large case series. Approach and Results: We collected data from cases in 18 countries. The type of liver injury was assessed with the R‐value. The study population was categorized according to features of immune‐mediated hepatitis (positive autoantibodies and elevated immunoglobulin G levels) and corticosteroid therapy for the liver injury. We identified 87 patients (63%, female), median age 48 (range: 18–79) years at presentation. Liver injury was diagnosed a median 15 (range: 3–65) days after vaccination. Fifty‐one cases (59%) were attributed to the Pfizer‐BioNTech (BNT162b2) vaccine, 20 (23%) cases to the Oxford‐AstraZeneca (ChAdOX1 nCoV‐19) vaccine and 16 (18%) cases to the Moderna (mRNA‐1273) vaccine. The liver injury was predominantly hepatocellular (84%) and 57% of patients showed features of immune‐mediated hepatitis. Corticosteroids were given to 46 (53%) patients, more often for grade 3–4 liver injury than for grade 1–2 liver injury (88.9% vs. 43.5%, p = 0.001) and more often for patients with than without immune‐mediated hepatitis (71.1% vs. 38.2%, p = 0.003). All patients showed resolution of liver injury except for one man (1.1%) who developed liver failure and underwent liver transplantation. Steroid therapy was withdrawn during the observation period in 12 (26%) patients after complete biochemical resolution. None had a relapse during follow‐up. Conclusions: SARS‐CoV‐2 vaccination can be associated with liver injury. Corticosteroid therapy may be beneficial in those with immune‐mediated features or severe hepatitis. Outcome was generally favorable, but vaccine‐associated liver injury led to fulminant liver failure in one patient. Abstract : SARS‐COV‐2 vaccination and liver injury.image